INFECTIVE ENDOCARDITIS IN THE PRESENCE OF HYPERTROPHIC CARDIOMYOPATHY: CLINICAL CASES - Ye. Yu. Ponomareva; N. M. Nikitina; S. V. Landfang (Klinicist)
The paper describes 2 cases that demonstrate the patterns and specific features of infective endocarditis in the presence of hypertrophic obstructive cardiomyopathy, diagnostic difficulties, comorbidities, as well as error analysis and a disease outcome